Synthesis of Isoindoline-1,3-Dione Derivatives as Cyclooxygenase (Cox) S Inhibitors: Pharmaceutical Science-Medicinal chemistry - Jaafar Al-Husseini; Zuhair Muhi-Eldeen; Sadeq Al-Tameemi; Rand Al-Qazweeny (International Journal of Life Science and Pharma Research, 2022)
Inflammation is the vital part of the immune system’s response to injury and infection. It is the body’s way of signaling the immune system to heal and repair damaged tissue. The objective of this paper is to design and synthesize a new isoindoline 1,3-dinoe derivative and investigate their selective anti inflammatory activity to COXs. As a potential anti-inflammatory compound, Isoindoline-1,3-dione derivatives were synthesized from the addition reaction of phthalimide, formaldehyde, catalytic amount of potassium hydroxide and cyclic amine in ethanol yielded the desired Isoindoline-1,3-dione compounds (ZJ1-ZJ6. 1H- NMR, ¹³C-NMR, FT-IR and elemental analysis were consistent with the assigned structures. Isoindoline-1,3-dione derivatives exhibited good inhibitory activity against the COX enzymes. To explain the result of our investigation to COX-1 and COX-2 and the selectivity of our compounds to either COX-1 or COX-2, the rationalization in COX-1, the amino group participate more effectively in binding with the ligand while in COX-2, the aryl group is more effective in binding to the ligand. The amino acetylenic compounds behave differently toward COXs from our compound. ZJ4 have shown some selective COX-1 ligand efficiency while ZJ1 promised a potent blockage and ligand efficiency toward the COX-2 enzyme which was found to be higher than the marketed drug Indomethacin and near potency score of Celecoxib. For the first time, this indicates the requirement of investigating the removal of acetylenic group in this study showed that it might be a different binding site in COXs which may result in effective compounds.